Η εκλογική διαδικασία και τα εκλογικά συστήματα (Μέρος 1ο) - ΙΩΑΝΝΗΣ ΠΑΠΑΓΕΩΡΓΙΟΥ (Αριστοτέλειο Πανεπιστήμιο Θεσσαλονίκης, 2022)
: You seem anyone lost game one loss but me T it will get Yeah or my enjoy what it means for is ve me the I need I need dual or you me you know here Ha the he E E I see you all right it really is made us and we need a me as his eing only all lose fire season what you leave your boy happy ran Shi how do we Melissa lee or Yes shear so maybe you're a little blew me Yeah I thing you're a gun coming with me you aces he Citi is more Evelyn any longer you know me is rule she's or or lower E the the Hayes Yeah all Yeah your wall there's all was movie role all or is slowly or you need me Pulse need he souls be cool my need days always one seen I see or you Yes Yes need T ER give us see you Anna Veith I need pieces you Yeah I love you I beef Rohde Yes you this Sony young may roll you'll have my World I needed boy is uses Yeah this knee he us a all easy me Yeah Yeah for me we do Yeah Yeah I need more I saw and each things you know me whole slew Yeah you'll you my releasing all these leap anything so boy Haiti's hair and what we've always T anymore you need Blue is not you know me Yeah Yeah malls you your you Yeah and beef said Dave should the these this all all the raw you're the bones your bullies you my Yeah Yeah Betty Les go out you all day this Yeah he Gay's role this so moment always need I when is the last is our World do you Yeah Yeah Hugh Yeah he ends bullet I see what heat Yes Yeah all this all these all border boy needs is for us the movie you need vote I just is she role what WA niche you my goal IU Mi G WU good you need a Yeah Yeah it your meal may these me ease of use you do go to for all she's for the new York ones yet the your sure all for you the years we hours moves you Hoeness loses we O of was well ou I use you blow the evening Yeah this you always need almost Hello or leave it is designed Yes O us you're a sleaze you owe polls what news all worries me nor bore ET the needs of knee all Manus love he what bull Natalee's being our each stall we see my about role I lose you earn you Yeah what we're year even this meaty roles you're almost home Yeah very missile is cool guy we knew Raul Shah lush love is Lucey Yes these these the Roy T cinched voices slow this you you'll see me review nieces for me this loss need bold guy he's my whole this me movie is it's smile me none of these you day baby Yeah one of the Yes Yes you saw ball the goal helium DC must Lou Yeah Ba us the most Yeah it the you he's really your is based human Yeah you shoes and needs your he's case you know you gave new should move old you only need he's Oh this is the I EJ I all the off these Yes use your home's mole all these years you alls you almost the one views Eales Yes easy 0 hazy is all only eat alls all we want Ga unit Yep the need I loans it's I do blow your O een the mole this even for mean mall I think Oh Yeah T quality all I need you alone is you me you need you Whoa Whoa beef next boy you've got almost fun v each miner will Whoa and loses feeds gains one for what is 80 you Yeah for sure you my enjoy us Wow loans he being 80 see savings and a whole lot more used by pmary bully me the rules the over my it and show he's today's Daesh you Mehdi me medium the movie me NASA's new movie you era you'll ishe it's a wound Yeah we need beef and go see hazing you that Daesh Daesh Oh man he's smooth you do or ease Jay-Z quo you don't see you're all it won't be made whole my movies our unity is all we want feed you zMe Yeah is this easy Blue we'll Yeah whole anyou we Olaf use S the move he he needs the you Yeah Yeah me read the me mom Max Yeah bar that Holmes was goals or use the each what we'll is is Yes I me came we need these my reasons I need my you need the all Yeah you belong it yet made mess homeowners you hold your Yeah what I I we dating you goal maybe one reason it needs to go God I was T is my you Whoa Whoa I need I more rose Bowl season neo I the plans Yeah lower woes that he more Zen they came man she was aware all Yeah is now on the issue of anis all 0 he's you so I she's Yes all of us were Yeah your is zoo Wohl or not all Yeah roles easy or me you're always me Williams Yes Lerner no we made you Where's your that wall is not move T each one Wow me he's Whoa 0 O Wash he's what he's veto hall over the Yeah WI be need Yeah this movie Wolf her all all my what this man Yeah Yeah I mean she wished Europe it's not moose or loses you Yeah I need sleep one year ja Yeah I S I'm all for a eating he's Yeah we this was Yeah Yeah movie the made all newly Lowry's needs me we're bull you Boo me Oh Woah lose rooms for Lou bull the uses this loves us in new York city so I knew it was you what was your work me what is the glue reince pool Yeah me made me and where this your we easy all these more you love me the man almost whether me it's this do so here we go all key just yet miss more us Yes Yes the he everything so both where you need movie is we me plus E Hayes Yes bonds you know there's Yes Yeah needs so you Hills is God give me the 0 homes you whose Yes you know the SMI needs not as you wounds these move he it's see moon singer love food maize the home me and normal or me the need and the love just love medicine home or not be these blows your always Yeah all she or now easy for anyone she need us Yeah you do whole for or is unique I days we're Hello new York one of these days when you I don't know yet LU Yo I know we will who Harlow member Sciutto now what he needs would you Yes where we need boom will meet hall 6 move we'll anymore the will of God booth was 80 blues Hall eyes the moment you want me to say me she you all and grown hard the years World is he losses you then is this I blew us need these mass choose and see Hey Te' o lonely I T uma now more me need Wow you see all bowls we're not us Neil what do all may be I easy my game young you we won't Dean uses lose or you this key need Yeah Yeah nice Hello he's baby you know our Whoa room Post parents knew see you Zick got wrong the move will Yes Yes sees holes we eating all I we needs vision all Yeah my blood seed goal he's movie easy Floyd O K C Hayes E Y it may see you I E G wo you need G she you or here Wolf you need ET me what Yeah me and my he saw what was the and Yes Yes all over I even amid all these you don't call me boy love snacks for do you so I think Hizbullah he's eats Yeah let me only you need eyes you ING's need day knee he's I mean he's me loves I ECG need eggs I eat eggs I assume it's Hayes you a see I a Yeah Yeah Yeah is all lies my move stage boy boy leave Yes role is if you're wound by is and is me for years I was game we old me & in a World of these must be bu you want there holes whole lot you 100 miles anybody he based not not your message for all mine always you use nobody all exit get it on the move follows this he's new niche you'll love this he's all you base all I role let me young I ING prices Ah we got these lives Yeah so at this it's my business was man man side td's need that in my 30 hole you're not I am inside always goals is may see what the road Yeah Yeah is receive Whoa go with me ask all you Yeah the means eat thee ball who moved always new with whether in the wild the little New York worry you lose you need me Moloney you Whoa Yeah eased need young he's the it we're moving en masse Sheesh your Yeah we'll be need you want your man he's wall v loss Yes v he need pulling for you and that is what we roof is you see Yes mom SMU's Yeah v avoid that's it for me buses on Yeah Yeah he See below for who so ball Sol 0 do only Ole Ole or believes all these young love is love is all you through all of these bosses Yeah so you believe these days goal hall Daesh with my bow grands need your cools you we love you man needs only use old we com for your